Comparison of Horizontal Displacement from Horizontal Control Network Adjustment Result Using Observation Model and Time-Variant Methods (Case Study : Horizontal Control Network of Borobudur Temple, Epoch 2002, 2003 and 2012) - Een Lujainatul Isnaini; Dwi Lestari (Jurnal Geospasial Indonesia, 2018)
Borobudur Temple is the biggest Buddhist Temple in the world protected by UNESCO. Therefore the periodical maintenance of Borobudur temple become important, deformation study through displacement analysis can be applied for it, by conducting Geodetic observation periodically. The design for Borobudur horizontal monitoring network is a relative one, the control point and monitoring points are in the deformation area. Therefore, the effect of position changes of the control point used in the horizontal network for displacement analysis of Borobudur needs to be considered, as it affects the result for the least square adjustment of the monitoring points. Two different adjustment methods used to overcome this problem, Least square adjustment using observation model and time-variant methods. This research aims to compare the horizontal displacement analysis of Borobudur resulted from these two adjustment methods.  First by giving position correction for the control point at each epoch according to its displacement in least square adjustment using observation model. The second by computing position and velocity vector directly using time-variant method. The comparation of 2D horizontal displacement vector analysis was done by using vector velocity of 2D horizontal displacement from the analysis of the two adjustment methods on the interval displacement epochs between 2002 and 2003 and between 2002 and 2012. This research showed the vector magnitude and the accuration of the displacement from the analysis resulted from the two adjustment methods was different. The resulted of least square adjustment using observation model with correction of control point showed that there was significant increase in magnitude of displacement vector of the monitoring points. Displacement analysis between 2002 and 2003 the magnitude in average were 7.97 mm and the analysis between 2002 and 2012 were 37.78 mmwith consistent displacement direction of the both interval displacement to the northwest. The Time-Variant adjustment method showed an increase in the vector velocity of 2D horizontal displacement from 0.29 mm/year to 0.32 mm/year with different displacement direction. The vector magnitude of the displacement from time variant method was smaller than observation model and the standard deviation for the horizontal displacement from time variant method was slightly bigger about 0.5 mm compared to the observation model.